Analysis of terminal schedule probes and schedule thinning effects following functional communication training. (11th November 2021) - Kranak, Michael P.; Falligant, John Michael
Abstract: Functional communication training (FCT) is a behavioral intervention that results in reduction of problem behavior and acquisition of adaptive communication responses. After FCT, schedule thinning is typically conducted to make community implementation of FCT more feasible. Specifically, the density of reinforcement for the alternative response is gradually decreased over time. It is plausible that one could avoid schedule thinning by proceeding to the terminal schedule thinning value without first systematically decreasing the density of reinforcement along the way. However, very little applied research exists in which the terminal schedule values are probed prior to schedule thinning. We conducted terminal schedule probes before schedule thinning and analyzed the relapse of problem behavior before and after schedule thinning. Rates of problem behavior in the terminal probes exceeded those in baseline in two out of three treatments prior to schedule thinning. Implications for clinical practice and future research are discussed.